Prevalence of allergic bronchopulmonary aspergillosis among patients with severe bronchial asthma in a tertiary care hospital in Northern India - D Bhankhur; N Singla; D Aggarwal; J Chander (Wolters Kluwer Medknow Publications, 2019)
Introduction: The link between fungi and asthma has been known for centuries. About one-third to one-half of severe asthmatics has history of atopic sensitization to filamentous fungi, most predominantly to Aspergillus fumigatus. Allergic bronchopulmonary aspergillosis (ABPA) is the one of the most documented fungal presentations among patients with asthma. This study was done on 50 patients with severe asthma who were consecutively enrolled from January 2016 to June 2017 to look for prevalence of ABPA. Materials and Methods: Blood samples were collected from 50 patients with severe asthma, and serum was separated to test for absolute eosinophil count, total IgE, and Aspergillus fumigates-specific IgE. Results: The prevalence of ABPA was found to be 70% (35/50). Of these, ABPA-B (ABPA with bronchiectasis) was less 31.4% (11/35) when compared with 68.5% (24/35) of patients with serological ABPA. Out of these 35 patients, there were 18 females and 17 were males. The mean age of the patients was 41.3 years. Conclusion: ABPA prevalence is high in patients with severe asthma, and there is a need to look for and evaluate this association further.